2018
DOI: 10.1097/iae.0000000000002195
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management of Pigment Epithelial Detachments in Eyes With Neovascular Age-Related Macular Degeneration

Abstract: A comprehensive literature search suggests that anti–vascular endothelial growth factor therapy is effective in treating eyes with pigment epithelial detachment due to neovascular age-related macular degeneration. This therapy should focus primarily on vision gains because there is no apparent correlation between anatomical and functional improvement in most eyes with pigment epithelial detachment and neovascular age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 49 publications
2
41
0
1
Order By: Relevance
“…The regression analysis in our current study showed similar results. A literature review also showed that fibrovascular PED was more resistant to antiangiogenic therapy and may be associated with a poorer visual outcome 30 . Additionally, pachychoroid neovasculopathy has also been described after the introduction of enhanced‐depth OCT, and many studies have compared the difference between CNV with or without pachychoroid.…”
Section: Discussionmentioning
confidence: 99%
“…The regression analysis in our current study showed similar results. A literature review also showed that fibrovascular PED was more resistant to antiangiogenic therapy and may be associated with a poorer visual outcome 30 . Additionally, pachychoroid neovasculopathy has also been described after the introduction of enhanced‐depth OCT, and many studies have compared the difference between CNV with or without pachychoroid.…”
Section: Discussionmentioning
confidence: 99%
“…A RPE tear may develop in 15% to 20% of eyes with PEDs after anti-VEGF therapy; however, vision may stabilize with continued therapy. Atrophy may complicate eyes with PED and nAMD after anti-VEGF therapy, especially in association with complete PED resolution [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of new onset or residual IRF is consistently associated with worse visual outcomes (Jaffe et al 2013; Lambert et al 2016). Similarly, PED can be associated with visual loss; therefore, current recommendation is that unstable PED or PED with concurrent IRF or SRF should be treated (Khanani et al 2018). Nevertheless, dietary β‐carotene intake was not significantly associated with VA over 12 months in this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%